Microarchitecture, but Not Bone Mechanical Properties, Is Rescued with Growth Hormone Treatment in a Mouse Model of Growth Hormone Deficiency. (13th March 2012) - Kristensen, Erika; Hallgrímsson, Benedikt; Morck, Douglas W.; Boyd, Steven K.
Abstract : Growth hormone (GH) deficiency is related to an increased fracture risk although it is not clear if this is due to compromised bone quality or a small bone size. We investigated the relationship between bone macrostructure, microarchitecture and mechanical properties in a GH-deficient (GHD) mouse model undergoing GH treatment commencing at an early (prepubertal) or late (postpubertal) time point. Microcomputed tomography images of the femur and L4 vertebra were obtained to quantify macrostructure and vertebral trabecular microarchitecture, and mechanical properties were determined using finite element analyses. In the GHD animals, bone macrostructure was 25 to 43% smaller as compared to the GH-sufficient (GHS) controls (P < 0.001 ). GHD animals had 20% and 19% reductions in bone volume ratio (BV/TV) and trabecular thickness (Tb.Th), respectively. Whole bone mechanical properties of the GHD mice were lower at the femur and vertebra (67% and 45% resp.) than the GHS controls (P < 0.001 ). Both early and late GH treatment partially recovered the bone macrostructure (15 to 32 % smaller than GHS controls) and the whole bone mechanical properties (24 to 43% larger than GHD animals) although there remained a sustained 27–52% net deficit compared to normal mice (P < 0.05 ). Importantly, early treatment with GH led to a recovery of BV/TV and Tb.Th with a concomitant improvement of trabecular mechanical properties. Therefore, the results suggest that GH treatment should start early, and that measurements of microarchitecture should be considered in the management of GHD.